THE PORTUGUESE TAX SYSTEM: COMPLEXITY AND ENFORCEABILITY - Lopes, Cidália Maria da Mota (Revista Universo Contábil, 2008)
This article provides an overall tax analysis of the complexity of the Portuguese tax system. Before discussing whether we should change the way we tax ourselves, it will be useful to compare the Portuguese tax system to other OCDE and European countries. However, the main aim of this study is to discuss the main aspects that make the Portuguese tax system complex and difficult to enforce. Then, in order to simplify the Portuguese tax system, we will focus on economic, administrative and legislative issues that have introduced some kind of complexity in the tax system.